Atmospheric Concentrations of Polycyclic Aromatic Hydrocarbons (PAHs) in India and South Korea: A Review - Narayana Suvarapu, Lakshmi; Baek, Sung-Ok (Mini-Reviews in Organic Chemistry, 2016)
Polycyclic aromatic hydrocarbons (PAHs) gain more attention from the researchers all over the world as compared to other air pollutants due to their carcinogenic, mutagenic and teratogenic nature to humans. The association of PAHs with the fine fraction of particulate matter is of significant importance in terms of persistence in the atmosphere, where they can undergo chemical reactions and also be transported to a long distance. In present study we reviewed the ambient concentrations of PAHs in India and South Korea from the published papers since 2012. From this study it is clear that the Indian people are exposing high amounts of PAHs than Koreans. For example, the highest concentration of Benzo[a]pyrene (carcinogen to humans) reported in Korea is 3.46 ng/m3 where as in India it is 1189 ng/m3. In this study, we tabulated and discussed the analytical parameters evaluated in the determination of atmospheric PAHs, such as sampling period, sampling device, extraction method, analytical instrument used and QA/QC measurements.
Keywords: Air pollutants